TOTAL BAKTERI PSIKOTROPIK IKAN NILA (Oreochromis niloticus) YANG DIBERI PENINGKATAN SUHU PADA SAAT PEMELIHARAAN (Total of Phsycotrophic Bacteria of Nile Tilapia (Oreochromis niloticus) Reared in High Water Temperature) - Safni Kamal; Nurliana Nurliana; Faisal Jamin; Sulasmi Sulasmi; Hamny Hamny; Fakhrurrazi Fakhrurrazi (Jurnal Medika Veterinaria, 2016)
This research aimed to calculate the number of phsycotrophic bacteria of nile tilapia reared in increased water temperature. For this purpose, 12 nile tilapias with body weight of 35-40 g were randomly allotted into 2 treatments groups with 3 replications. Fish in group 1 (P1) was reared in normal temperature (29±1° C) and group II (P2) was reared in high water temperature (35±1 C). All fish were fed commercial diet 3 times a day for 21 consecutive days. T-test analysis revealed a significant decrease in number of psychotropic bacteria (P0.01) in group P2. Total plate count (TPC) resulted in fish gills, intestinal, and muscle were 1.5×10³, 7.7x10³, and 9.7x10³ cfu/g respectively. In conclusion, increasing of water temperature reduce the number of phsycotrophic bacteria of nile tilapia.